Can device closure of AP window be made easy? - Chandrakant, Chavan; A., Parkar Matin; Rajesh, Badani; G., Pawar Shubhadarshini (International Journal of Advances in Medicine, 2017)
Aortopulmonary window is an uncommon congenital cardiac defect. Most infants presenting with aortopulmonary window will undergo conventional surgical repair. Experience with transcatheter closure of aortopulmonary window is limited. We report the case of a 5-year-old boy with aortopulmonary window, in whom transcatheter closure was performed successfully using Amplatzer ductal occluder device.